2021
DOI: 10.3389/fpubh.2021.672061
|View full text |Cite
|
Sign up to set email alerts
|

How Can I Feel Safe at Home? Adolescents' Experiences of Family Violence in Ghana

Abstract: Despite the implementation of various national legal frameworks and global policies such as the UN Convention on the Rights of the Child to combat violence against young people, family violence against young people is prevalent, especially in WHO African region. Although, research on child maltreatment, specifically, for young children has received considerable attention in Ghana recently, there is little research on adolescents' experiences of such family violence. In this paper, we report the experiences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…The negligent behavior of caregivers is generally attributed to a lack of emotional attachment 6 , which is in line with the findings of this study. In relation to the family, various aspects can favor or interfere with the process of forming an affective bond and protecting children and adolescents, such as previous experiences of violence and mistreatment by parents or caregivers, revealing the need to understand the patterns of intergenerational transmission of the problem in order to prevent it 16 .…”
Section: " (C3)supporting
confidence: 92%
See 1 more Smart Citation
“…The negligent behavior of caregivers is generally attributed to a lack of emotional attachment 6 , which is in line with the findings of this study. In relation to the family, various aspects can favor or interfere with the process of forming an affective bond and protecting children and adolescents, such as previous experiences of violence and mistreatment by parents or caregivers, revealing the need to understand the patterns of intergenerational transmission of the problem in order to prevent it 16 .…”
Section: " (C3)supporting
confidence: 92%
“…Their early exposure to these situations can trigger damage and aggravation of a biopsychosocial nature, resulting in deficits in their growth and development 3,4 . As a consequence, short-and long-term impacts can be seen in the lives of this population, such as post-traumatic stress 5,6 , symptoms of insomnia, shorter sleep duration and nightmares 7 and permanent disability 6 , requiring continuous interventions in order to provide for the wellbeing of future generations of victimized children and adolescents 5 . Considering these impacts, the Sustainable Development Goals call for an end to abuse, exploitation and all forms of violence and torture against them by 2030 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Exposing children to Intimate Partner Violence (IPV) is also recognized as a form of child maltreatment [8]. At the family level, adolescents can experience violence in the forms of physical (use of physical force with intent to harm others), psychological (verbal or gestural with the intention of humiliating, threatening, or causing damage to self-esteem), and sexual violence (the imposition of sexual practice against the wishes of an individual or which results in their victimization), exploitation (use of the child in work or other activities for the benefit of others, which harms, for example, the child's physical and mental health and education), neglect (lack or denial of care to those in need) and exposure to intimate partner violence (experiencing violence between intimate partners) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, UNICEF reported that about 3.4 million Ghanaian children experienced an emotional or physical assault during childhood. Also, approximately 90% of children in Ghana experienced some form of abuse before reaching adulthood (3). According to the Ghana Family Life and Health Survey, nearly 28% of women experienced either of the four types of domestic violence (physical, sexual, emotional and economic) 12 months preceding 2015 (4).…”
Section: Introductionmentioning
confidence: 99%